Morbidity pattern and health seeking behavior in elderly population of Raipur City, Chhattisgarh, India - Naushad, Md. Alam; Verma, Nirmal; Bhawnani, Dhiraj; Jain, Meeta; Anand, Tanu; Umate, Laxmikant V. (Indian Journal of Community Health, 2016)
Background: Epidemiological transition across globe is considered as the net result of the demographic transition. The shape of the population pyramid is gradually changing from a wide-based and narrow topped form to a barrel-shaped form in recent future (1). Aims & Objectives: 1. To determine morbidity pattern in elderly population, 2. To assess their health care seeking behavior. Material & Methods: Study design- A Community based cross sectional observational study. Study setting - Pt J.N.M. Medical College, Raipur, Chhattisgarh. Study Duration: July 2013 to June 2014. Sampling method: - Multi stage simple random sampling. Sample size: 640. Sample Size were calculated by using statistical formula, n= Z21-?/2 P(1-P)/d. Study tool: Pre-designed, Pre-tested Performa. Ethical consideration-Written document from institutional ethical Committee and Informed Consent from subject. Inclusion criteria: 1. All elderly persons in the age group of 60 years and above who were residing in the study area for at least one year, and willing to Participate in study without compulsion. Exclusion Criteria: 1. Those who were not willing to participate in study. Results & Conclusions: Prevalence of morbidity was 95.31%. Morbidity was positively associated with advancement of age and predominant in females (98.92%) and those belong to slum (98.43%) and lower (98.14%) socio-economic status while inversely associated with Physical activity. Out of total morbid population 70.49% had chronic illness. Most common system involvement was Gastro intestinal system (82.62%). Perception about illness was increased with advancement of age. Majority were seeking therapy from private registered practitioner (35.52%).